(untitled) (Sustainability in Debate, 2017)
Type III ecolabel has been adopted by many countries in the world, especially after the demands of European countries. The increased adoption of type III ecolabel and elaboration of rules to categorize products in various productive sectors have been observed. Brazil, recently has published an environmental product declaration (EPD) program (Programa de Rotulagem tipo III-DAP) regulated by the National Metrology, Quality and Technology Institute (Instituto Nacional de Metrologia, Qualidade e Tecnologia ”“ INMETRO), also responsible for Brazil’s life cycle analysis program. This article identified and analyzed instruments, challenges, limits and possibilities to implement the program proposed by INMETRO for type III ecolabel, based on international experience, SWOT analysis and interviews with industry actors. It was concluded that INMETRO’s program is recent but aligns well with other programs around the world, allowing a possible mutual recognition in the future. Moreover, the Brazilian program can be integrated to other public policies, strengthening its own implementation.